Tantalum-tungsten alloy microstructure morphology corrosive liquid and use method thereof

By using a corrosion solution composed of aqua regia, hydrofluoric acid, hydrogen peroxide and sulfuric acid, and using a multi-mechanical attack method, the problem of low corrosion efficiency of the existing tantalum and tungsten alloy corrosion solution is solved, and efficient and stable microstructure morphology display is achieved.

CN119824420APending Publication Date: 2025-04-15NORTHWEST INSTITUTE FOR NONFERROUS METAL RESEARCH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510150490.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-11
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The corrosion efficiency of existing tantalum and tungsten alloy corrosion liquid is low, and the microstructure morphology of tantalum and tungsten alloy cannot be clearly displayed. It is complicated to prepare and cumbersome to operate.

Method used

The corrosion liquid composed of aqua regia, hydrofluoric acid, hydrogen peroxide and sulfuric acid is used to destroy the passivation film of tantalum and tungsten alloy through multi-mechanism attacks of Cl-pitting, H+ acid corrosion and oxidant dissolution, and control the dynamic balance of corrosion, and the microstructure structure is clear.

Benefits of technology

It has achieved efficient display of the grain boundaries, grains and deformation structure of tantalum and tungsten alloy, simplified the preparation and use of corrosion liquid, improved corrosion efficiency and stability, and ensured a clear display of microstructure morphology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119824420A_ABST
    Figure CN119824420A_ABST
Patent Text Reader

Abstract

The invention discloses a tantalum-tungsten alloy microstructure morphology corrosive liquid and a using method thereof. The corrosive liquid is composed of aqua regia, hydrofluoric acid, hydrogen peroxide and sulfuric acid. The using method comprises the following steps: 1, preparing a tantalum-tungsten alloy microstructure morphology corrosive liquid; secondly, the ground and polished metallographic sample is placed in a tantalum-tungsten alloy microstructure morphology corrosive liquid to be etched; and 3, taking out, cleaning, drying, and observing under a metallographic microscope. According to the corrosive liquid, a synergistic effect is achieved through component design, a passivation film of the tantalum-tungsten alloy is attacked and damaged through multiple mechanisms, corrosion dynamic balance is controlled, a microstructure is kept clear, and the microstructure is highlighted through phase selective dissolution of acid, so that the corrosion resistance of the tantalum-tungsten alloy is improved on the premise that the microstructure is not damaged. The method has the advantages of high efficiency, easiness in control, simplicity in use, high efficiency and wide application range, and is suitable for the technical field of metal detection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal detection, and in particular relates to a tantalum-tungsten alloy microstructure morphology etching liquid and a use method thereof. Background Art

[0002] Tantalum has excellent physical and chemical properties, such as high melting point and high density, good corrosion resistance and low temperature plasticity. Adding tungsten to tantalum can form a tantalum-tungsten solid solution alloy. Tungsten plays a good solid solution strengthening role in tantalum-tungsten alloy. The room temperature tensile strength and strain hardening rate of the alloy increase significantly with the increase of tungsten content. Tantalum alloy with high tungsten content has the characteristics of high density, high melting point, corrosion resistance, good processability and weldability. It is an indispensable and important material in the fields of aerospace, chemical industry, nuclear industry and high temperature technology, and has a good application prospect.

[0003] While having excellent corrosion resistance, tantalum-tungsten alloy also poses corresponding challenges to detection methods. Conventional metallographic etching liquids are basically unable to efficiently etch tantalum-tungsten alloy metallographic specimens, and there are problems such as long etching time, low efficiency, unclear grain boundary structure, and uneven corrosion of microstructure morphology. Through metallographic testing, we can understand information about the crystal structure, alloy composition, heat treatment state, and mechanical properties of metal materials. This information helps to reveal the properties and defects of the alloy and provide a theoretical basis for improving alloy performance and technology. In addition, the existing tantalum-tungsten alloy metallographic etching liquid and its use method still have problems such as troublesome preparation and cumbersome grinding and polishing procedures. Therefore, how to prepare a simple and efficient tantalum-tungsten alloy microstructure morphology etching liquid and seek corresponding methods of use are problems that still need to be solved in the current field of tantalum-tungsten alloy detection technology. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a tantalum-tungsten alloy microstructure morphology etching solution in view of the deficiencies of the above-mentioned prior art. The etching solution plays a synergistic role through component design, uses multiple mechanisms to attack and destroy the passivation film of the tantalum-tungsten alloy, and controls the dynamic balance of corrosion to keep the microstructure clear, and combines the phase selective dissolution of the acid to highlight the microstructure structure, so as to efficiently display the grain boundaries, grains and deformation structures of the tantalum-tungsten alloy without destroying the microstructure, thereby solving the problem that the existing tantalum-tungsten alloy etching solution has low corrosion efficiency and poor corrosion effect, which makes it difficult to clearly display the microstructure.

[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: a tantalum-tungsten alloy microstructure morphology etching solution, characterized in that it is composed of the following components: aqua regia, hydrofluoric acid, hydrogen peroxide and sulfuric acid.

[0006] Aiming at the characteristics of dense and stable passive film on the surface of tantalum-tungsten alloy and excellent corrosion resistance, the etching solution of the present invention adopts aqua regia, hydrofluoric acid, hydrogen peroxide and sulfuric acid as components, wherein the aqua regia contains hydrochloric acid and nitric acid, hydrochloric acid provides Cl- to destroy the passive film on the surface of tantalum-tungsten alloy, causing pitting and selective corrosion, nitric acid has strong oxidizing property, promotes the oxidation of the surface of tantalum-tungsten alloy into soluble salt (such as nitrate), and has selective destroying effect on the passive film of tantalum-tungsten alloy; hydrofluoric acid can dissolve oxides containing tantalum and titanium, and is suitable for tantalum-tungsten alloy; hydrogen peroxide, as a strong oxidant, releases active oxygen (O), accelerates the oxidation reaction of tantalum-tungsten alloy, and synergistically enhances the corrosion efficiency with acid; sulfuric acid, as a strong acid, provides H+, promotes the dissolution of tantalum-tungsten alloy, and has dehydrating property, accelerates the stripping of oxide film, and enhances the oxidizing ability of oxidants (such as nitric acid and hydrogen peroxide). Therefore, the corrosive liquid of the present invention exerts a synergistic effect after acting on the tantalum-tungsten alloy. First, Cl- is adsorbed on the surface of the passivation film to form a local micro-battery, which triggers pitting corrosion and destroys the passivation film on the surface of the tantalum-tungsten alloy. At the same time, the H+ in the corrosive liquid reduces the pH and accelerates the dissolution of the tantalum-tungsten alloy matrix. The oxidant oxidizes the metal to generate a soluble salt by strengthening the reaction, thereby avoiding the regeneration of the passivation film. The hydrofluoric acid specifically dissolves the tantalum oxide in the tantalum-tungsten alloy, exposing the microstructure of the tantalum-tungsten alloy matrix.

[0007] The above-mentioned tantalum-tungsten alloy microstructure morphology etching solution is characterized in that it is composed of aqua regia, 40% by mass hydrofluoric acid, 30% by mass hydrogen peroxide and 95% to 98% by mass sulfuric acid in a volume ratio of 0.8 to 1.2:0.8 to 1.2:0.8 to 1.2:1.2 to 1.6.

[0008] The above-mentioned tantalum-tungsten alloy microstructure morphology etching solution is characterized in that it is composed of aqua regia, 40% by mass hydrofluoric acid, 30% by mass hydrogen peroxide and 95% to 98% by mass sulfuric acid in a volume ratio of 1:1:1:1.5.

[0009] At the same time, the present invention also discloses a method for using the above-mentioned tantalum-tungsten alloy microstructure morphology etching solution, characterized in that the method comprises the following steps:

[0010] Step 1: prepare tantalum-tungsten alloy microstructure morphology etching solution;

[0011] Step 2: placing the ground and polished metallographic sample in the tantalum-tungsten alloy microstructure morphology etching solution prepared in step 1 for etching;

[0012] Step 3: Take out the metallographic sample after etching in step 2, clean and dry it, and then observe it under a metallographic microscope.

[0013] The existing methods for using etching liquid usually have the following problems: the etching liquid ratio needs to be precisely controlled, the operation steps are cumbersome, and repeated experiments are required to determine the optimal parameters, which is time-consuming and labor-intensive. At the same time, the results are unstable, the corrosion effect is greatly affected by environmental factors, and the repeatability is poor. The present invention optimizes the etching liquid ratio and simplifies the operation process, has the advantages of fewer steps, shorter time, and easy to use. The metallographic sample after etching has clear and continuous grain boundaries, complete grain morphology, and no over-corrosion or under-corrosion phenomenon. At the same time, the corrosion effects of different batches of samples are consistent and highly repeatable, thereby achieving efficient and stable corrosion effects.

[0014] The above-mentioned method of use is characterized in that the process of preparing the tantalum-tungsten alloy microstructure morphology etching solution in step 1 is: adding aqua regia, hydrofluoric acid, hydrogen peroxide and sulfuric acid in sequence and stirring evenly.

[0015] The above-mentioned method of use is characterized in that the grinding process described in step 2 is: select a coarse sandpaper in the range of 400# to 800#, select a fine sandpaper in the range of 1200# to 2000#, and then grind from coarse to fine in sequence until the surface to be observed is parallel and uniform sandpaper grinding marks. The existing grinding method usually uses multi-level sandpaper for step-by-step grinding (such as from 200#→400#→600#→800#→1000#→1500#→2000#). Each time the sandpaper is replaced, the surface of the sample must be thoroughly cleaned to avoid coarse particles remaining and affecting the subsequent grinding effect. The grinding method has the following problems: ① The sandpaper needs to be replaced many times, which is complicated and time-consuming; ② The grinding time of each level of sandpaper is long, and the overall preparation cycle is extended; ③ Frequent operation is easy to introduce scratches or contamination, affecting the quality of the sample. The present invention simplifies multi-stage grinding into two-stage grinding by optimizing sandpaper selection and grinding process. The specific improvements are as follows: ① Use a single coarse sandpaper to quickly remove surface macroscopic defects (such as cutting marks and oxide layers) to lay the foundation for subsequent fine grinding; ② Use a single fine sandpaper for fine grinding to eliminate the scratches left by the coarse sandpaper and obtain a smooth and flat surface. The two-stage sandpaper grinding process of the present invention ensures a smooth transition of the two-stage grinding by adjusting the grinding pressure, speed and direction, avoids local over-grinding or under-grinding, significantly simplifies the preparation process of tantalum-tungsten alloy metallographic samples, and greatly improves the preparation efficiency while ensuring the surface quality.

[0016] The above-mentioned method of use is characterized in that the grinding directions of the coarse sandpaper and the fine sandpaper are perpendicular to each other.

[0017] The above-mentioned method of use is characterized in that the polishing process described in step 2 is: select synthetic fiber cloth, felt cloth or cotton cloth as the polishing cloth, select chromium oxide, aluminum oxide or silicon dioxide as the polishing agent, and perform polishing until the surface to be observed is a mirror surface. The existing polishing process usually uses a single polishing cloth and a universal polishing agent, which has the following problems: ① It takes a long time to eliminate sandpaper marks, especially for tantalum-tungsten alloys with high hardness and toughness, the polishing time may be as long as 30 minutes to 60 minutes; ② Scratches, tailing or contamination are easily generated during the polishing process, affecting the clear display of the microstructure. The present invention achieves efficient and high-quality polishing effects through the coordinated optimization of polishing cloth and polishing agent. The specific improvements are as follows: ① Select a polishing cloth with high elasticity and high wear resistance (such as synthetic fiber cloth, felt cloth or cotton cloth), whose surface is evenly distributed with microporous structure, which can effectively absorb the polishing agent and evenly transmit pressure to avoid local over-polishing or under-polishing; ② Use chromium oxide, aluminum oxide or silicon dioxide suspension as a polishing agent, whose high hardness and uniform dispersion can quickly remove surface micro-protrusions to obtain a smooth surface; ③ By adjusting the polishing pressure, rotation speed and time, a balance between polishing efficiency and surface quality is achieved to avoid overheating or over-polishing. The present invention quickly eliminates sandpaper grinding marks and shortens the polishing time through the coordinated optimization of polishing cloth and polishing agent, obtains a bright mirror surface without scratches and pollution, meets the requirements of high-magnification microscopic observation, and significantly improves the efficiency and quality of the polishing process; at the same time, this method is not only applicable to tantalum-tungsten alloys, but can also be extended to the metallographic preparation of other difficult-to-process materials (such as titanium alloys and nickel-based high-temperature alloys).

[0018] The above-mentioned method of use is characterized in that the etching time in step 2 is 60s to 120s.

[0019] The above-mentioned method of use is characterized in that the cleaning in step three is carried out using running water or anhydrous ethanol.

[0020] Compared with the prior art, the present invention has the following advantages:

[0021] 1. The etching solution of the present invention uses aqua regia, hydrofluoric acid, hydrogen peroxide and sulfuric acid as components, and utilizes the synergistic effect of each component to perform multi-mechanism attack through Cl- pitting + H+ acid etching + oxidant dissolution, destroy the passivation film of tantalum-tungsten alloy from multiple angles, break through its corrosion resistance, and reduce over-corrosion through oxidants to control the dynamic balance of corrosion, keep the microstructure clear, and combine the phase selective dissolution of tantalum-containing specific phases through acid to highlight the microstructure. Under the reasonable ratio of the components of the etching solution, the etching solution can efficiently display the grain boundaries, grains and deformation structures of tantalum-tungsten alloy without destroying the microstructure, providing key information for material analysis.

[0022] 2. Compared with the existing tantalum-tungsten alloy etching solution with mixed acid as component, the etching solution of the present invention controls the ratio of acid to oxidant in the components and continuously supplies oxygen to maintain the oxidizing environment, so that the corrosion rate tends to be constant, realizes the dynamic balance of corrosion, improves the reaction stability with the tantalum-tungsten alloy metallographic sample, and preferentially corrodes the high-energy grain boundaries through the synergistic effect of Cl- and the oxidant, reduces the corrosion rate of the tantalum-tungsten alloy matrix by 30% to 50%, and makes the grain morphology sharper, so that the microstructure is clearly displayed, the grain boundary / grain contrast is enhanced, and the grains and grain boundaries of the microstructure morphology of the tantalum-tungsten alloy can be clearly displayed. At the same time, HF selectively dissolves specific oxides to avoid the "pitting" problem; in addition, the etching solution of the present invention can efficiently corrode and avoid the risk of over-corrosion, and can flexibly adjust the corrosion depth by dilution or time gradient. It has the advantages of high efficiency and easy controllability, and has a wide range of uses. It provides a new solution for the characterization of tantalum-tungsten alloys and is suitable for the field of metal detection technology.

[0023] 3. The etching solution of the present invention has simple ingredients and is easy to prepare. The corrosion degree of the tantalum-tungsten alloy can be easily controlled by adjusting the erosion time of the etching solution, thereby clearly displaying the microstructure grains and grain boundary morphology to varying degrees according to observation requirements. It has strong practicality and high application value.

[0024] 4. Compared with the traditional continuous grinding method, the sandpaper grinding process of the present invention is shorter, and only any coarse sandpaper and any fine sandpaper need to be selected to complete the grinding, which greatly simplifies the grinding steps of tantalum tungsten alloy and improves the preparation efficiency of metallographic samples.

[0025] 5. The polishing cloth and polishing agent used in the polishing process of the present invention can quickly eliminate the sandpaper polishing marks generated in the grinding process and obtain a bright mirror surface to be observed, further improving the preparation efficiency of the metallographic sample.

[0026] 6. The method for using the etching solution of the present invention is simple and easy to use, and greatly improves the efficiency of the microstructure morphology analysis of tantalum-tungsten alloy.

[0027] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a microstructure morphology diagram of the tantalum-tungsten alloy metallographic sample in Example 1 of the present invention.

[0029] Figure 2 This is a microstructure morphology diagram of the tantalum-tungsten alloy metallographic sample in Example 2 of the present invention.

[0030] Figure 3 This is a microstructure morphology diagram of the tantalum-tungsten alloy metallographic sample in Example 3 of the present invention. DETAILED DESCRIPTION

[0031] Example 1

[0032] The tantalum-tungsten alloy microstructure morphology etching solution of this embodiment is composed of aqua regia, 40% by mass hydrofluoric acid, 30% by mass hydrogen peroxide and 95% to 98% by mass sulfuric acid in a volume ratio of 0.8:0.8:0.8:1.2.

[0033] The method for using the tantalum-tungsten alloy microstructure morphology etching solution of this embodiment comprises the following steps:

[0034] Step 1: add aqua regia, hydrofluoric acid, hydrogen peroxide and sulfuric acid in sequence, and stir evenly to prepare a tantalum-tungsten alloy microstructure morphology etching solution;

[0035] Step 2: Use 400# coarse sandpaper and 1200# fine sandpaper to grind the tantalum-tungsten alloy metallographic sample from coarse to fine in sequence, and the grinding directions of the coarse sandpaper and the fine sandpaper are perpendicular to each other, until the surface to be observed is parallel and uniform sandpaper grinding marks, then use synthetic fiber cloth as polishing cloth, and use chromium oxide as polishing agent to polish the tantalum-tungsten alloy metallographic sample after grinding until the surface to be observed is a mirror surface, and then place the tantalum-tungsten alloy metallographic sample after grinding and polishing in the tantalum-tungsten alloy microstructure morphology etching solution prepared in step 1 for etching for 60s;

[0036] Step 3: Take out the metallographic sample after etching in step 2, wash it with running water and dry it, and then place it under a metallographic microscope for microstructure observation and analysis.

[0037] Figure 1 The microstructure morphology of the tantalum-tungsten alloy metallographic sample in this embodiment is shown in FIG. Figure 1 It can be seen that under the mild corrosion condition of the etching solution of this embodiment, the microstructure of the tantalum-tungsten alloy metallographic sample is mainly equiaxed grains, and grain boundaries and subgrain boundaries begin to appear.

[0038] Example 2

[0039] The tantalum-tungsten alloy microstructure morphology etching solution of this embodiment is composed of aqua regia, 40% by mass hydrofluoric acid, 30% by mass hydrogen peroxide and 95% to 98% by mass sulfuric acid in a volume ratio of 1:1:1:1.5.

[0040] The method for using the tantalum-tungsten alloy microstructure morphology etching solution of this embodiment comprises the following steps:

[0041] Step 1: add aqua regia, hydrofluoric acid, hydrogen peroxide and sulfuric acid in sequence, and stir evenly to prepare a tantalum-tungsten alloy microstructure morphology etching solution;

[0042] Step 2: Use 600# coarse sandpaper and 1500# fine sandpaper to grind the tantalum-tungsten alloy metallographic sample from coarse to fine in sequence, and the grinding directions of the coarse sandpaper and the fine sandpaper are perpendicular to each other, until the surface to be observed is parallel and uniform sandpaper grinding marks, then choose felt cloth as polishing cloth, choose aluminum oxide as polishing agent, polish the tantalum-tungsten alloy metallographic sample after grinding, until the surface to be observed is a mirror surface, and then place the tantalum-tungsten alloy metallographic sample after grinding and polishing in the tantalum-tungsten alloy microstructure morphology etching solution prepared in step 1 for etching for 90s;

[0043] Step 3: Take out the metallographic sample after etching in step 2, clean it with anhydrous ethanol and dry it, and then place it under a metallographic microscope for microstructure observation and analysis.

[0044] Figure 2 The microstructure morphology of the tantalum-tungsten alloy metallographic sample in this embodiment is shown in FIG. Figure 2 It can be seen that under the appropriate corrosion conditions of the preferably proportioned etching solution in this embodiment, the etching solution selectively dissolves the grain boundary region of the tantalum-tungsten alloy metallographic sample, exposing the grain morphology, with clear and continuous grain boundaries and distinct grain contours; under high magnification, the complete morphology of equiaxed grains can be seen, the grain boundary width is uniform, there is no obvious over-corrosion phenomenon, and slight subgrain boundaries can be seen inside some grains.

[0045] Example 3

[0046] The tantalum-tungsten alloy microstructure morphology etching solution of this embodiment is composed of aqua regia, 40% by mass hydrofluoric acid, 30% by mass hydrogen peroxide and 95% to 98% by mass sulfuric acid in a volume ratio of 1.2:1.2:1.2:1.6.

[0047] The method for using the tantalum-tungsten alloy microstructure morphology etching solution of this embodiment comprises the following steps:

[0048] Step 1: add aqua regia, hydrofluoric acid, hydrogen peroxide and sulfuric acid in sequence, and stir evenly to prepare a tantalum-tungsten alloy microstructure morphology etching solution;

[0049] Step 2: Use 800# coarse sandpaper and 2000# fine sandpaper to grind the tantalum-tungsten alloy metallographic sample from coarse to fine in sequence, and the grinding directions of the coarse sandpaper and the fine sandpaper are perpendicular to each other, until the surface to be observed is parallel and uniform sandpaper grinding marks, then use cotton cloth as polishing cloth, and use silicon dioxide as polishing agent to polish the tantalum-tungsten alloy metallographic sample after grinding until the surface to be observed is a mirror surface, and then place the tantalum-tungsten alloy metallographic sample after grinding and polishing in the tantalum-tungsten alloy microstructure morphology etching solution prepared in step 1 for etching for 120s;

[0050] Step 3: Take out the metallographic sample after etching in step 2, clean it with anhydrous ethanol and dry it, and then place it under a metallographic microscope for microstructure observation and analysis.

[0051] Figure 3 The microstructure morphology of the tantalum-tungsten alloy metallographic sample in this embodiment is shown in FIG. Figure 3 It can be seen that the etching solution of this embodiment effectively dissolves the grain boundaries and intragranular regions of the tantalum-tungsten metallographic phase sample, the equiaxed grains are clear, the grain boundary corrosion is wide, and obvious subgrain boundary etching features are visible inside the grains, which is suitable for observing intragranular defects or substructure analysis at high magnification.

[0052] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A tantalum-tungsten alloy microstructure morphology etching solution, characterized in that: It is composed of the following ingredients: aqua regia, hydrofluoric acid, hydrogen peroxide and sulfuric acid.

2. The tantalum-tungsten alloy microstructure morphology etching solution according to claim 1 is characterized in that: The invention is composed of aqua regia, hydrofluoric acid with a mass fraction of 40%, hydrogen peroxide with a mass fraction of 30% and sulfuric acid with a mass fraction of 95% to 98% in a volume ratio of 0.8 to 1.2:0.8 to 1.2:0.8 to 1.2:1.2 to 1.

6.

3. The tantalum-tungsten alloy microstructure morphology etching solution according to claim 2 is characterized in that: The product is composed of aqua regia, 40% by mass hydrofluoric acid, 30% by mass hydrogen peroxide and 95% to 98% by mass sulfuric acid in a volume ratio of 1:1:1:1.

5.

4. A method for using the tantalum-tungsten alloy microstructure morphology etching solution as claimed in any one of claims 1 to 3, characterized in that: The method comprises the following steps: Step 1: prepare tantalum-tungsten alloy microstructure morphology etching solution; Step 2: placing the ground and polished metallographic sample in the tantalum-tungsten alloy microstructure morphology etching solution prepared in step 1 for etching; Step 3: Take out the metallographic sample after etching in step 2, clean and dry it, and then observe it under a metallographic microscope.

5. The method of use according to claim 4, characterized in that: The process of preparing the tantalum-tungsten alloy microstructure morphology etching solution in step 1 is: adding aqua regia, hydrofluoric acid, hydrogen peroxide and sulfuric acid in sequence and stirring evenly.

6. The method of use according to claim 4, characterized in that: The grinding process described in step 2 is: select a coarse sandpaper in the range of 400# to 800#, select a fine sandpaper in the range of 1200# to 2000#, and then grind from coarse to fine in sequence until the surface to be observed has parallel and uniform sandpaper grinding marks.

7. The method of use according to claim 6, characterized in that: The grinding directions of the coarse sandpaper and the fine sandpaper are perpendicular to each other.

8. The method of use according to claim 4, characterized in that: The polishing process in step 2 is: select synthetic fiber cloth, felt cloth or cotton cloth as the polishing cloth, select chromium oxide, aluminum oxide or silicon dioxide as the polishing agent, and perform polishing until the surface to be observed is a mirror surface.

9. The method of use according to claim 4, characterized in that: The etching time in step 2 is 60s to 120s.

10. The method of use according to claim 4, characterized in that: The cleaning described in step 3 is performed using running water or anhydrous ethanol.

Citation Information

Cited By

  • Tungsten-nickel-tantalum alloy microstructure morphology corrosive liquid and application thereof

    CN121951539A